AUDIT OF END OF LIFE DISCUSSIONS IN PATIENTS WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE. Issue Volume 4: Issue (2014)Supplement 1 (1st March 2014) - Arnold, David; Cheaveau, Matthew; Beard, Charlie; Reid, Colette
Abstract : Background: The NHS End of Life Care Council advises that end of life (EoL) discussions should be offered to patients with chronic obstructive pulmonary disease (COPD) who have certain poor prognostic markers. EoL conversations with advanced care planning can reduce a patient's anxiety during an exacerbation, allow informed decisions about what treatment they would (or would not) like to receive in the future, reduce unnecessary or unwanted hospital admissions, and enable patients to die in their preferred place. Aims: To assess whether patients who are admitted to a respiratory ward with exacerbations of COPD, who fulfill the criteria, have been offered the opportunity to have such discussions. Secondary aims included (i) patient engagement, (ii) communication of outcomes (iii) communication of DNACPR orders. Methods: Audit of all patients admitted to a respiratory ward with an exacerbation of COPD, within a 3 month period. Specifically looking for evidence of EoL conversations during the current admission, previous admission or clinic appointments. Results: Of 48 patients admitted with an exacerbation of COPD, 20 fulfilled the criteria to be offered EoL conversations. The 3 month mortality of these 20 patients was 25%. Three patients (15%) had documented EoL conversations. One lead to the formation of an advance directive not to return to hospital, one described a patient's wish to have no further non-invasive ventilation, and one where a patient wanted full treatment escaltion in the future. Seventeen of the 20 patients were made DNACPR, however, only 4 had this communicated to the GP. Recommendations: Identify patients on hospital board rounds that may be suitable for end of life discussions. If patients engage with EoL discussions this should be documented in the medical notes as well as the discharge summary. Further use of an existing "Poor prognostic indicators" letter, which is sent to the GP, noting engagement in EoL discussions and decisions around DNACPR orders.